High Rate of Studies with Level 1 and 2 Evidence among the 100 Most Cited Articles in Lumbar Spinal Stenosis - Martínez-Andrés, Juan; Ayala-Gascón, María; Mariscal, Gonzalo; Alfonso-Beltrán, Joaquín; Barrios, Carlos (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2021)
Background To date, no study has used bibliometric analysis to review the most influential articles in lumbar spinal stenosis. The objective of this study was to identify and analyze the characteristics and the level of evidence of the 100 most cited articles on lumbar spinal stenosisMethods The Thomson Reuters Web of Science was accessed to find the 100 most cited articles on lumbar spinal stenosis. For each article, we recorded the number and density of citations, authors, country, journals and years, department, level of evidence, type of study, and if it was part of any multicenter studies.Results Until January 2017, the 100 most cited articles accumulated 11,136 citations (average: 259.05/y), ranging individually between 442 and 50 (average: 111.36). The first reference was published in 1974 in Clinical Orthopaedics and Related Research. Therapeutic studies (n = 40), the 1990s (n = 46), United States as country of origin (n = 51), Harvard University as institution (n = 16), Katz JN as author (n = 10), and Spine as journal (n = 48) have the hegemony. Many were multicenter (n = 42) and using level 2 evidence (n = 49). There is an inverse relationship between citation index and long-standing studies, maintenance of those most cited, and a temporary advance toward better levels of evidence.Conclusion This bibliometric analysis reveals a good level of evidence in the published clinical series and includes 100 articles useful for the approach of lumbar spinal stenosis.
Keywords: bibliometric analysis; spine research; citation analysis; lumbar spinal stenosis; most cited